Discourse of totalitarianism in the interpretation by V. Vynnychenko and G. Orwell (based on novels «It’s Your Word Now, Stalin!» and «1984») - Промська, Альона Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article aims to investigate the specificity of the artistic presentation of totalitarianism discourse in novels «It’s Your Word Now, Stalin!» by V. Vynnychenko and «1984» by G. Orwell through typological comparison of literary works and ideological positions of the writers. The author draws parallels between the biographical realities and their artistic interpretation in the writings by novelists. The study helps to identify and explore holistically the peculiarities of V. Vynnychenko’s and G. Orwell’s philosophical and aesthetic approaches to the representation of such important categories in their works as state and personality, democracy and terror, personality and mass, opportunities for humanity to achieve happiness in the totalitarian world. The theme of war and peace is a leitmotif for the creative works of both artists, in particular for novels «It’s Your Word Now, Stalin!» and «1984». However in contrast to V. Vynnychenko who showed the horror of Stalinism in the USSR focusing on the impleentation of the idea of «сollectocracy» that would eliminate all wars on the planet, G. Orwell created the image of «superstate» that embodied both features of Hitlerism and Stalinism, and author’s reflections on the evolution of totalitarianism in the world and its consequences for humanity in the future. Representing in the novels a miserable world of the totalitarian state that invalidates personalities, turning them into weak-willed mass of mediocrities, the English writer aimed to warn the world of totalitarian aggression. Instead the Ukrainian artist created the image of country of concentration camps and secret informers, proposing alternative model of the society without terror — his own idea of «сollectocracy» which implementation could not only destroy the wage labor but also prevent any conflict on the planet.